At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

The solution of the equation 2x - 7 = 3x - 12 is _____ Since it checks in the original equation, it is also a solution of
StartRoot 2x-7 EndRoot - StartRoot 3x - 12 EndRoot = 0.



The Solution Of The Equation 2x 7 3x 12 Is Since It Checks In The Original Equation It Is Also A Solution Of StartRoot 2x7 EndRoot StartRoot 3x 12 EndRoot 0 class=

Sagot :

Answer:

5

Step-by-step explanation:

2x-7=3x-12

2x-3x=-12+7

-x=-5

x=5

[tex] \sqrt{2x - 7} - \sqrt{3x - 12 } = 0 \\ \sqrt{10 - 7} - \sqrt{15 - 12} = 0 \\ \sqrt{3} - \sqrt{3} = 0[/tex]